Sea surface temperature simulation and forecast. Issue 2 (3rd March 2016) - Tarakanov, Alexander O.; Borisova, Alla V.
Abstract : Unconventional computing of sea surface temperature (SST) was once featured by NASA as a unique merger of science and art . Our approach led to a discovery that just one geographical point could be sufficient to track global anomalies of SST based on El Niño Southern Oscillation (ENSO). Such single point in the Pacific Ocean off of the island of Isabella in the Galapagos Islands was named the Galapagos indicator . Now we show that a single point in the Baltic Sea off of the coast of Göteborg could be also sufficient to track ENSO. We propose to name it the Baltic indicator . We also demonstrate that two crisis falls of oil price in 2008 and 2014 followed just after the local maximums of Baltic indicator. However, Baltic and Galapagos indicators do not show any evident trend in settling the global warming from the beginning of this century.